A computational investigation of the interaction between As3+ and deoxynucleotides. Issue 10 (3rd July 2019) - Yu, Huaxing; Yuan, Min; Cao, Hui; Ye, Tai; Yu, Jinsong; Xu, Fei
ABSTRACT: A successful aptamer biosensor for As 3+ in aqueous solution indicated that deoxynucleotides could be a potential ligand for arsenic absorption. However, the interaction mechanism between aptamer and As 3+ is still not clear. In this paper, a density functional method was applied to investigate the interactions between As 3+ and four kinds of deoxynucleotides in different charge states. According to the binding energy, dGMP was the best monomer with four different binding modes, and dGMP 3– As 3+ with the O atom in the phosphate group was calculated to be the most stable one. Moreover, the interaction energy increased when the charge of deoxynucleotide was increased, suggesting that a negative charge was advantageous for deoxynucleotides to absorb As 3+ . The atoms in molecules (AIM), localised orbital locator (LOL) and Charge decomposition analyses (CDA) confirmed that the bond between N atoms and As 3+ were covalent interactions and that between O atoms and As 3+ were dominated by electrostatic interactions. As the charge grew, the bond strength of both interactions increased. At the same time, O atom in the vicinity of nucleobases began to participate in the interaction with As 3+, which was originally bonded to N atoms.